Eddy Induced Cross-Shelf Exchanges in the Black Sea - Anıl Akpınar; Ehsan Sadighrad; Bettina A. Fach; Sinan Arkın (Remote Sensing, 2022)
Cross-shelf exchanges in the Black Sea were investigated using remote sensing data and an ocean circulation model to which an eddy-tracking algorithm and Lagrangian particle tracking model was applied. An anticyclonic eddy in 1998 and a cyclonic eddy in 2000 were investigated in detail. Eddy-induced cross-shelf transport of low salinity and high Chl-a waters reached a maximum in the presence of filaments associated with these eddies. The daily mean volume transport by the eddies was comparable with the previously documented transport by eddies of similar size in the north-western shelf region. Lagrangian particle tracking results showed that 59% of particles initially released over the shelf were transported offshore within 30 days by the 1998 anticyclone and 27% by the 2000 cyclone. The net volume transport across the Black Sea shelf-break reached the maxima in winter, coinciding with the increase in wind stress curl and mean kinetic energy that is a measure of the intensity of the boundary current. Ekman transport directly influences the cross-shelf exchanges in the surface layer. The south-eastern Black Sea is presented as an important area for cross-shelf transport. The total cross-shelf transport can be divided into its “large-scale” and “eddy-induced” components. Eddy-induced transport was 34% and 37% of the total cross-shelf transport (1998–2014) in the Black Sea in the off-shelf and on-shelf directions, respectively, but these values ranged between 25% and 65% depending on the eddy activity over time.